2016
DOI: 10.1051/0004-6361/201526765
|View full text |Cite
|
Sign up to set email alerts
|

FORS2/VLT survey of Milky Way globular clusters

Abstract: Context. Globular clusters trace the formation and evolution of the Milky Way and surrounding galaxies, and outline their chemical enrichment history. To accomplish these tasks it is important to have large samples of clusters with homogeneous data and analysis to derive kinematics, chemical abundances, ages and locations. Aims. We obtain homogeneous metallicities and α-element enhancement for 51 Galactic bulge, disc, and halo globular clusters that are among the most distant and/or highly reddened in the Gala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
133
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(160 citation statements)
references
References 51 publications
27
133
0
Order By: Relevance
“…These values are consistent with previous spectroscopic and photometric estimates that ranged from [Fe/H]∼−0.75 to −0.90 dex (Zinn 1980;Bica & Pastoriza 1983;Ortolani et al 2001;Valenti et al 2005Valenti et al , 2011Dias et al 2016) and indicate that NGC 6569 is a relatively metalrich globular cluster. Valenti et al (2011) prevented a more detailed analysis, and they were not able to confirm whether the cluster exhibits the usual light-element abundance correlations.…”
Section: Metallicity Distribution Functionsupporting
confidence: 92%
“…These values are consistent with previous spectroscopic and photometric estimates that ranged from [Fe/H]∼−0.75 to −0.90 dex (Zinn 1980;Bica & Pastoriza 1983;Ortolani et al 2001;Valenti et al 2005Valenti et al , 2011Dias et al 2016) and indicate that NGC 6569 is a relatively metalrich globular cluster. Valenti et al (2011) prevented a more detailed analysis, and they were not able to confirm whether the cluster exhibits the usual light-element abundance correlations.…”
Section: Metallicity Distribution Functionsupporting
confidence: 92%
“…For member stars, we found an average RV of −16.07 km s −1 (with σ = 3.98). This value is in excellent agreement with the average RV (−16.7 km s −1 , σ = 5.5) found by S15 from two stars, but not with the older literature value (−45.1 km s −1 ) listed in Harris (1996Harris ( , 2010, as already discussed in S15, or with the value of −29.6 (σ = 39.1) km s −1 in Dias et al (2016), that was however obtained on much-lower-resolution spectra.…”
Section: Flames Spectrasupporting
confidence: 91%
“…Finally, Dias et al (2016) analysed spectra of nine stars in the wavelength range 4560-5860 Å, at a resolution approximately 2000. They measured radial velocities (RV) and found that eight of the stars are members of the cluster; they also determined atmospheric parameters, iron and Mg (or alpha) abundance ratios using a comparison with stellar libraries.…”
Section: Ngc 5634 In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…We have three stars in common with Tang (Table 2) -their results for these stars are compatible with our results taking into account the errors. Dias et al (2016) studied the low-resolution optical spectra of the same stars from Saviane et al (2012). They used a full-spectrum fitting technique to derive the abundance.…”
Section: Ironmentioning
confidence: 99%